Current status of sport performance in Boccia: systematic review of the literature - Cátia Ferreira; José Gamonales; Mario André da Cunha Espada; Jesús Muñoz-Jiménez (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Boccia is a Paralympic sport, also practiced in a recreational perspective by the population. Performance in this parasport involves complexity. Hence, the aim of this study was to conduct a review of the literature on Boccia, specifically in the field of sports performance. Keywords “Boccia” and “Performance” were used as descriptors in the references search. The words in English were introduced in the Web of Science, PubMed, Scopus and Google Scholar databases. 669 documents were found using the word “Boccia” and after including the word “Performance” results reduced to 26 documents. Three exclusion criteria were applied: i) Documents not published in scientific journals; ii) Documents do not mention in title or abstract both “Boccia” and “Performance”; and iii) Documents are thesis, chapters of books, conference resumes or abstract. Finally, 9 documents were selected that met the inclusion and exclusion criteria until February 2022. Results confirmed that research in Boccia is scarce compared to other sports to persons with disabilities. Therefore, the Paralympic sport has been analysed from a great diversity of disciplines perspective, however, regarding the discipline “Coaching Science” there is a great space and need for further research, in order to improve training conditions and optimize sports performance.